CRITICAL HISTORY, SUBVERSION AND SELF-SUBVERSION: THE CURIOUS CASES OF JEAN MABILLON AND RICHARD SIMON (II/II) - Veronica LAZĂR (Studia Universitatis Babeș-Bolyai. Philosophia, 2020)
Jean Mabillon and Richard Simon were both eminent seventeenth-century scholars who practiced contextualizing critical philology in order to forge unbeatable scientifical instruments against the skeptics and reinforce the authority of historical documents. But Simon’s work produced a mutation of the meaning of authenticity that would prove subversive and would generate outrage. His sociological and institutionalist understanding of the history of sacred texts not only merged both their production and their transmission into a common, ontologically homogenous historical process, but also included a survey of the sociological and cultural circumstances that transformed the text into a real authority. Furthermore, this anti-essentialist understanding of the gradual formation of the text allowed a positive reevaluation of the tradition as a continuous practice aiming at keeping alive an already historical truth.